A service-oriented approach to modeling and performance analysis of Port Community Systems. (5th April 2018) - Nota, Giancarlo; Bisogno, Marco; Saccomanno, Antonello
A Port Community System (PCS) is an electronic platform that links the multiple systems operated by private and public organizations. Accordingly, PCSs can be interpreted as complex service system networks that coproduce services. The study proposes a three levels top-down methodology which aims to interpret existing PCS in order to: provide a formal description of this system network based on the enterprise architecture concepts of a PCS; illustrate how each actor of a PCS offers or requires services; and present a new approach to the measurement of services based on the Goal-Question-Metric paradigm.